Cloning and mapping of Saccharomyces cerevisiae photoreactivation gene PHR1. - Schild, D (1984)
The yeast Saccharomyces cerevisiae, like most organisms, is able to directly repair pyrimidine dimers by using a photoreactivating enzyme and visible light. Cells carrying the phr1 mutation were shown previously to be unable to photoreactivate dimers, but neither the map position nor the primary gene product of the PHR1 gene has been determined. We have cloned this gene and determined its map position. A plasmid containing a 6.4-kilobase yeast DNA insert has been isolated and shown to restore photoreactivation in a phr1 strain. A 3.1-kilobase subclone has also been shown to complement phr1. The original plasmid was targeted to integrate into chromosomal DNA at a site homologous to the insert by cutting within the insert. Two of these integrants have been mapped on the right arm of chromosome XV; the integrants have been further mapped at ca. 13 centimorgans from prt1. It has also been independently determined that phr1 maps at this location. Thus, we have determined the map position of PHR1 and also have shown that the plasmid contains PHR1 rather than a suppressor of the phr1 mutation.